2016
DOI: 10.1111/evj.12590
|View full text |Cite
|
Sign up to set email alerts
|

Influence of commonly used pharmaceutical agents on equine bone marrow‐derived mesenchymal stem cell viability

Abstract: Clinicians can sedate horses and administer nerve blocks to assist in intratendinous or intrathecal injection of MSCs with confidence that these drugs will not impact the viability of implanted cells. However, the concomitant use of corticosteroids is likely to have a severely detrimental effect on cell viability and should not be performed. Similarly, steroid administration into the sheath of a damaged tendon is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…However, Goodrich et al reported that the combination of MSCs and PRP enhance bone formation instead of cartilage in osteochondral defects created on the lateral trochlear ridge of the stifle (19). Although no practitioners reported combining corticosteroids with cell therapies, it is important to mention that adding methylprednisolone or triamcinolone to MSC cultures in vitro resulted in the rapid death of MSCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, Goodrich et al reported that the combination of MSCs and PRP enhance bone formation instead of cartilage in osteochondral defects created on the lateral trochlear ridge of the stifle (19). Although no practitioners reported combining corticosteroids with cell therapies, it is important to mention that adding methylprednisolone or triamcinolone to MSC cultures in vitro resulted in the rapid death of MSCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of incubation with the aforementioned treatment groups, the media and aggregates were collected separately, snap frozen in liquid nitrogen and stored at −80 • C for further analyses. The concentrations of MPA evaluated in this study were based on previous studies measuring corticosteroid-induced biosynthesis in equine chondrocytes (28,29), corticosteroid dose divided by the average estimated volume of navicular bursa/distal interphalangeal joint (8,30), and preliminary data collected in our laboratory.…”
Section: Aggregate Culturementioning
confidence: 99%
“…MSCs (Bohannon et al, 2013;Edmonds et al, 2016). Since the anesthetics and antibiotics form an important part of the in vivo cellular implantation, effect of these agents has to be determined for dMSCs also.…”
Section: Effect Of Available Culture Environmentmentioning
confidence: 99%